A symbiotic gut bacterium enhances Aedes albopictus resistance to insecticide. - Haiyang Wang; Hongmei Liu; Hui Peng; Yang Wang; Chongxing Zhang; Xiuxia Guo; Haifang Wang; Lijuan Liu; Wenxiang Lv; Peng Cheng; Maoqing Gong (Public Library of Science (PLoS), 2022)
Background The increasing insecticide resistance of Aedes albopictus puts many countries in Asia and Africa, including China, at great risk of a mosquito-borne virus epidemic. To date, a growing number of researches have focused on the relationship between intestinal symbiotic bacteria and their hosts' resistance to insecticides. This provides a novel aspect to the study of resistant mechanisms. Methods/findings This study reveals significant composition and dynamic changes in the intestinal symbiotic bacteria of Ae. albopictus between the resistant and susceptible strains based on full-length sequencing technology. The relative abundance of Serratia oryzae was significantly higher in the resistance strain than in the susceptible strains; also, the relative abundance of S. oryzae was significantly higher in deltamethrin-induced Ae. albopictus than in their counterpart. These suggested that S. oryzae may be involved in the development of insecticide resistance in Ae. albopictus. To explore the insecticide resistance mechanism, adult mosquitoes were fed with GFP-tagged S. oryzae, which resulted in stable bacterial enrichment in the mosquito gut without affecting the normal physiology, longevity, oviposition, and hatching rates of the host. The resistance measurements were made based on bioassays as per the WHO guidelines. The results showed that the survival rate of S. oryzae-enriched Ae. albopictus was significantly higher than the untreated mosquitoes, indicating the enhanced resistance of S. oryzae-enriched Ae. albopictus. Also, the activities of three metabolic detoxification enzymes in S. oryzae-enriched mosquitoes were increased to varying degrees. Meanwhile, the activity of extracellular enzymes released by S. oryzae was measured, but only carboxylesterase activity was detected. HPLC and UHPLC were respectively used to measure deltamethrin residue concentration and metabolite qualitative analysis, showing that the deltamethrin degradation efficiency of S. oryzae was positively correlated with time and bacterial amount. Deltamethrin was broken down into 1-Oleoyl-2-hydroxy-sn-glycero-3-PE and 2',2'-Dibromo-2'-deoxyguanosine. Transcriptome analysis revealed that 9 cytochrome P450s, 8 GSTs and 7 CarEs genes were significantly upregulated. Conclusions S. oryzae can be accumulated into adult Ae. albopictus by artificial feeding, which enhances deltamethrin resistance by inducing the metabolic detoxification genes and autocrine metabolic enzymes. S. oryzae is vertically transmitted in Ae. albopictus population. Importantly, S. oryzae can degrade deltamethrin in vitro, and use deltamethrin as the sole carbon source for their growths. Therefore, in the future, S. oryzae may also be commercially used to break down the residual insecticides in the farmland and lakes to protect the environment.